Behavioral Activation for mexican women victims of violence during the COVID-19 Pandemic: a non-randomized pilot study (Brazilian Journal of Behavioral and Cognitive Therapy, 2023)
Objective: To evaluate depressive symptoms and levels of behavioral activation in telehealth for women victims of violence (VCM) during the COVID-19 pandemic. Method: A quasi-experimental pretest-posttest design without a control group was used. The participants were 14 women (18-60 years old) with depression and victims of violence. The Beck Depression Inventory and the Behavioral Activation for Depression Scale were applied. Participants were recruited through social networks and a culturally adapted protocol of Brief Behavioral Activation Treatment for Depression (BATD) was applied in telehealth, once a week. Data were analyzed with the Wilcoxon signed-rank test and Reliable Change Index. Results: There was a decrease in depressive symptoms (p < .001) and an increase in activation levels (p < .001). Conclusions: BATD could be an effective treatment for women with depressive symptoms facing VCM in vulnerable contexts such as the COVID-19 pandemic.
Keywords: depression; violence against women; behavioral activation; COVID-19